3D Robotics : disrupting the drone market - Stuart, Toby; Anderson, Chris (London : SAGE Publications Ltd, 2017)
This case study focuses on 3D Robotics, a drone company with UAV platforms. The case study focuses on what 3DR should pursue at its critical inflection point within its history. The case study highlights what is unique about 3DR, particularly when compared to a more traditional non-open, non-Maker company.
Originally published: Stuart, T., & Anderson, C. (2015). 3D Robotics: Disrupting the drone market. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; 3D Robotics; Robot industry -- United States -- Case studies; Robotics -- United States -- Case studies